TEACHER COMPETENCE AND ORGANIZATIONAL COMMITMENT EFFECTS ON PERFORMANCE: MEDIATED BY READINESS FOR MERDEKA CURRICULUM IMPLEMENTATION - Masduki Masduki; Nik Haryanti (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study examines the effects of professional competence, organizational commitment, and teacher readiness on teacher performance in implementing the Kurikulum Merdeka. A quantitative research design was employed, involving 119 teachers of MAN in East Java as respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that professional competence and teacher readiness have positive, significant direct effects on teacher performance, whereas organizational commitment does not. However, professional competence and organizational commitment both significantly affect teacher readiness, which in turn mediates their influence on teacher performance. These results indicate that teacher readiness plays a crucial mediating role in strengthening performance outcomes. The study implies that improving teacher performance in implementing the Kurikulum Merdeka requires strategic efforts to enhance professional competence and foster organizational conditions that build teachers’ readiness, including supportive work environments, clear role expectations, and a constructive organizational climate.